A brief instrument measuring the water, sanitation and hygiene domain of menstrual health among women who inject drugs. - Alhelí Calderón-Villarreal; Lourdes Johanna Avelar Portillo; Daniela Abramovitz; Shira Goldenberg; Shawn Flanigan; Penelope J E Quintana; Alicia Harvey-Vera; Carlos F Vera; Gudelia Rangel; Steffanie A Strathdee; Georgia L Kayser (PLoS ONE)
Background Domains of adequate menstrual health (MH) include access to water, sanitation, and hygiene (WASH). People who menstruate with social disadvantages-such as homelessness or drug injection practices-often face barriers to WASH access. However, validated instruments to measure MH are limited among marginalized populations, and available instruments involve lengthy surveys. We developed and evaluated psychometric properties of a novel 'MH WASH Domain Scale-12' among people who menstruate and who inject drugs in the Tijuana-San Diego region and identified correlates of MH access using this scale. Methods We constructed a MH-scale based on access to twelve WASH-related items: (1) menstrual products, (2) body hygiene (bathing per week), (3) water sources for bathing, (4) improved, (5) non-shared, (6) available, (7) private, (8) nearby, (9) and safe sanitation facilities, (10) availability of soap, (11) water source for handwashing, and (12) handwashing facilities with soap/water. Variables were dichotomized and summed, with scores ranging from 0-12 points and higher scores indicating better MH access. We assessed the scale's reliability and construct and content validity using data from a binational cross-sectional study. The sample included people who inject drugs (PWID) who had ever menstruated in their lifetime and were 18+ during 2020-2021. MH-WASH items were described, and the scale was further used as an outcome variable to identify correlates. Results Among 125 (124 cis-female and 1 trans-male) PWID that reported menstruating, our 'MH WASH Domain Scale-12' was reliable (Cronbach's alpha = 0.81, McDonald's Omega total = 0.83) and valid. We identified two sub-domains: Factor-1 included items describing 'WASH availability' and Factor-2 contained items related to 'WASH security'-encompassing physical and biological safety. Scale scores were significantly lower among participants experiencing unsheltered homelessness compared to participants experiencing sheltered homelessness or living in permanent housing. Conclusion We constructed and validated a novel and reliable scale to measure MH-related WASH access that can be used to assess MH among marginalized populations in English- and Spanish-speaking contexts. Using this scale we identified disparities in MH-WASH access among PWID and who menstruate in the US-Mexico border region.